Self‐Sensing Actuators: Graphene Mesh for Self‐Sensing Ionic Soft Actuator Inspired from Mechanoreceptors in Human Body (Adv. Sci. 23/2019). Issue 23 (4th December 2019) - Tabassian, Rassoul; Nguyen, Van Hiep; Umrao, Sima; Mahato, Manmatha; Kim, Jaehwan; Porfiri, Maurizio; Oh, Il‐Kwon
Abstract : In article number 1901711, Il‐Kwon Oh and co‐workers propose a new sensing mechanism for measuring the actuation displacement of ionic actuators using a graphene mesh. Inspired by the mechanoreceptor in the human body, a graphene mesh is embedded inside the actuator membrane to record the change of electrical potential due to ion movement during actuation. This signal is then correlated with the movement of the actuator which also caused by ion migration inside the membrane.